Asset allocation and section 529 plans - Ramon P. DeGennaro (Federal Reserve Bank of Atlanta, 2003)
Previous research has concluded that prespecified asset allocations used by many Section 529 college savings plans are suboptimal. We extend this research to show that though it may be true, it is true for reasons other than those asserted in previous research. In addition, it tends to deflect attention from other investment options and strategies.
Keywords: 330; Investments; Saving and investment